RAḌĀ’AH IN THE QUR’AN: THE RELATIONSHIP OF UNDERSTANDING AND PRACTICE OF BREASTFEEDING AMONG MOTHERS IN ULEE KARENG, BANDA ACEH, INDONESIA - Nurullah, Nurullah; Zaini, Muhammad; Jamila, Cut Nurul (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2024)
The Qur’an in Surah al-Baqarah verse 233 emphasizes that the breastfeeding (raḍā’ah) period is two full years for those who want to perfect it; however, raḍā’ah up to two full years is not yet popular among Indonesian people and its prevalence is unknown. This study aims to explore the level of understanding, level of practice and relationship between understanding and practice of raḍā’ah among breastfeeding mothers in Ulee Kareng Subdistrict, Banda Aceh, Aceh Province. This field study used an analytical survey with a cross-sectional design. Data were collected by distributing questionnaires to 54 respondents, and the sample was determined using the Frank Lynch formula. The data were then analyzed using SPSS 20. The data for the first and second research questions were analyzed descriptively and quantitatively by calculating the average scores and percentages. The data for the third question were analyzed using the Crosstab facility using the Spearman Rank Correlation Test inferential statistics. The results showed that the level of understanding of breastfeeding mothers in Ulee Kareng regarding raḍā’ah was high with an average value of 3.29 and the level of practice was also high with an average value of 3.37. The relationship between the understanding of and the practice of raḍā’ah among breastfeeding mothers in Ulee Kareng indicates a significant relationship with a significance value of 0.000 (<0.05), in which Ha was accepted and H0 was rejected. The correlation coefficient value of 0.844 signifies a very strong relationship between mothers’ understanding and breastfeeding practice in Ulee Kareng Subdistrict, Banda Aceh.